Analisis Ikon Pada Cerpen “Gubrak!” Karya Seno Gumira Adjidarma - Andra Muhamad Rizky; Resti Suparti (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
This study aims to analyze a short story entitled "Gubrak!" by Seno Gumira Ajidarma using Charles Sanders Pierce's Semiotics approach. Pierce developed a theory of semiotics involving three main elements: sign, object, and interpretant. Pierce's semiotic theory provides an in-depth understanding of how language signs are used to represent objects in the real world as well as how meaning is generated through the interpretation of these signs. But the author only focuses on one of them, namely on the Icon contained in the short story. We found several marker icons in the short story "Gubrak!" by Seno Gumira that we can analyze together.